Kajang; A Picture of Modesty: An Indonesian Local Belief - Andi Akifah; Mukrimin Mukrimin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
The unique of Kajang ethnic is interesting to be studied by different disciplines. Their belief on the messages stated in â€œPasanga ri Kajangâ€ drive their step in running their life simply and wisely. This paper explores the community of Kajang and their religious beliefs and values. The importance of the Pasanga ri Kajang and the existence of Ammatoa as they believe as the messenger are two things that maintain their strong values and believes. Although they claimed to be Muslims, their religious practices are much different with general Muslims. They believe that â€œjeâ€™ne temmapettu; sembayang tellara,â€ which is meant, more or less, â€œunbreaka-ble ritual ablution and a never ending prayersâ€ as more important than the ritual religious practice. The concept is not primarily by the principles of Islam, but rather it is based on their attitudes and behaviors of daily life on traditional teachings supporting practices, such as â€œkalumbusuangâ€ (honesty); â€œgattangâ€ (consistency); â€œsabbaraâ€ (patience); and â€œappisonaâ€ (sincerity).